2021
DOI: 10.3390/safety7040066
|View full text |Cite
|
Sign up to set email alerts
|

Are Traffic Announcements Really Effective? A Systematic Review of Evaluations of Crash-Prevention Communication Campaigns

Abstract: Communication campaigns are commonly used in the traffic and road safety sector to raise public awareness of the importance of avoiding risky road user attitudes and behaviors. Surprisingly few of these communication campaigns evaluate their effectiveness in a formal and comprehensive manner. The core aim of the present systematic review is to identify the type of studies that evaluate the effectiveness of campaigns in this sector, in order to identify and contrast their main findings. This systematic review f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 66 publications
0
38
0
Order By: Relevance
“…Fixed speed cameras should also be installed on high accident risk roads. Furthermore, Road safety communication campaigns should be organized frequently, which had been confirmed that the effectiveness of communication campaigns was substantially increased if they are accompanied by other preventive measures such as legislation (51).…”
Section: Discussionmentioning
confidence: 90%
“…Fixed speed cameras should also be installed on high accident risk roads. Furthermore, Road safety communication campaigns should be organized frequently, which had been confirmed that the effectiveness of communication campaigns was substantially increased if they are accompanied by other preventive measures such as legislation (51).…”
Section: Discussionmentioning
confidence: 90%
“…A solid safety culture requires open and honest communication between drivers and supervisors [ 103 ]. Second, safety training assists oil and gas drivers in understanding safe behaviours and expectations [ 104 , 105 ]. Third, involve drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these results are relevant to the integration of useful information in expanding interventions and training designed to reduce risky behavior and promote road safety. Indeed, as highlighted in the systematic review by Faus et al (2021) , studies revealed that intervention programs are more effective when several different countermeasures, such as educational programs, simulator-based driver trainings, improvement in legislation, and increase in police control, are associated. Moreover, communication strategies employed in advertising campaigns have different outcomes on different samples of population, being less effective in drivers more prone to risky behaviors, that is, those road users whose behavioral change would be most desirable ( Faus et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as highlighted in the systematic review by Faus et al (2021) , studies revealed that intervention programs are more effective when several different countermeasures, such as educational programs, simulator-based driver trainings, improvement in legislation, and increase in police control, are associated. Moreover, communication strategies employed in advertising campaigns have different outcomes on different samples of population, being less effective in drivers more prone to risky behaviors, that is, those road users whose behavioral change would be most desirable ( Faus et al, 2021 ). Furthermore, the recall of these kinds of intervention seems very low in some countries, and varies on the basis of educational level, age, sex, and income ( Alonso et al, 2021 ), which suggest the need to replace the intervention on the basis of follow-up studies.…”
Section: Discussionmentioning
confidence: 99%